Birth Settings in America: Outcomes, Quality, Access, and Choice. Issue 3 (May 2020) - Simpson, Kathleen Rice
Abstract : A comprehensive report on birthing in the United States offers a detailed analysis of available choices, access to various choices, and associated risks for mother and baby. Consensus is lacking among researchers and clinicians on absolute and relative risks of adverse outcomes when comparing hospital, birth center, and home as a setting for birth. The National Academies of Science, Engineering and Medicine convened a committee of experts to examine these issues and prepare a summary of the evidence. The work of the committee was funded by the National Institute of Child Health and Human Development in response to congressional legislation sponsored by the Maternity Care Caucus including Congresswoman Lucille Roybal-Allard and Congresswoman Jaime Herrera Beutler.